Analysis of Cargo Handling Procedures Implementation to Minimize Cargo Shrinkage on SC Majestic LXII Vessel - Erfin Khidayat Artfan; Muhammad Thamrin; Rully Indrawan; Aswanti Setyawati Setyawati (Dinasti Review, 2025)
In distributing fuel oil in Indonesia, of course it requires a large mode of transportation that can distribute fuel oil in large quantities. One of these modes of transportation is sea transportation. Tankers are made to be able to carry liquid cargo which has sensitive properties and requires special treatment. Starting from loading, holding, loading on the ship, handling cargo on board and when unloading. The fact that researchers discovered on the SC Majestic XLII ship was that after unloading at Daesan port, Korea on January 21 2022, there was a Cargo Loss on the Naphtha cargo. The results of the load calculation after unloading are different from the calculation results after loading. Where the calculation results after the ship was unloaded, the land figure was 82,246,807 Barrels, while the calculation results at the loading port according to the Bill of Lading (a document that states the quantity of tanker cargo intended for the recipient party) was 82,400,783 barrels, the ship experienced a Cargo Loss the R4 figure (the difference in cargo from the reject port tank to the arrival port tank) is 153,976 barrels or 0.186%. This research is qualitative research with a descriptive approach. It is hoped that the research results can be compiled become a reference for the development of knowledge regarding the application of loading and unloading procedures to reduce cargo shrinkage.